Service users’ response to increased public services: Results from a randomized field experiment in education - Andersen, Simon Calmar; Nielsen, Helena Skyt; Thomsen, Mette Kjærgaard (Politica, 2015)
Recent studies indicate that service users may respond to increased investments in the public service production (in education) by lowering their contribution to the service production. This is unfortunate as it reduces the overall effect of increased public investments. However, coproduction theory suggests that service users’ response depends on whether they perceive the increased public effort as complementary to their own input or as a substitute. In a randomized field experiment in primary education we examined the behavioral response of service users to three different, but comparable public initiatives. In one initiative, the academically weakest students were assigned significantly more homework in an attempt to involve their parents in helping them with homework. According to our results, the children experienced that their parents did help them more. This suggests that if the design of such public initiatives makes service users perceive their contribution as a complement to the public effort the effect can be strengthened rather than weakened.